Comparison of the Greek Version of the Quick Mild Cognitive Impairment Screen and Standardised Mini-Mental State Examination. (10th August 2020) - Messinis, Lambros; O'Donovan, Mark R; Molloy, D William; Mougias, Antonis; Nasios, Grigorios; Papathanasopoulos, Panagiotis; Ntoskou, Aikaterini; O'Caoimh, Rónán
Abstract: Introduction: Short cognitive screening instruments (CSIs) are widely used to stratify patients presenting with cognitive symptoms. The Quick Mild Cognitive Impairment (Q mci ) screen is a new, brief (<5mins) CSI designed to identify mild cognitive impairment (MCI), which can be used across the spectrum of cognitive decline. Here we present the translation of the Q mci into Greek (Q mci -Gr) and its validation against the widely-used Standardised Mini-Mental State Examination (SMMSE). Methods: Consecutive patients aged ≥55 years presenting with cognitive complaints were recruited from two outpatient clinics in Greece. All patients completed the Q mci -Gr and SMMSE and underwent an independent detailed neuropsychological assessment to determine a diagnostic classification. Results: In total, 140 patients, median age 75 years, were included; 30 with mild dementia (median SMMSE 23/30), 76 with MCI and 34 with subjective memory complaints (SMC) but normal cognition. The Q mci -Gr had similar accuracy in differentiating SMC from cognitive impairment (MCI & mild dementia) compared with SMMSE, area under the curve (AUC) of 0.84 versus 0.79, respectively; while accuracy was higher for the Q mci -Gr, this finding was not significantly different, ( p = .19). Similarly, the Q mci -Gr had similar accuracy in separating SMC from MCI, AUC of 0.79 versus 0.73 ( p = .23). Conclusions: The Q mci -Gr compared favorably with the SMMSE. Further research with larger samples and comparison with other instruments such as the Montreal Cognitive Assessment is needed to confirm these findings but given its established brevity, it may be a better choice in busy clinical practice in Greece.